Pendampingan Pembuatan Bisnis Model Canvas sebagai Upaya Perintisan Agrobisnis dan Agroeduwisata Anggrek - Juartini, Tini; Butar, Florida Butar; Assidiq, Muhammad Nurhasan; Hadiwijaya, Syarif; Adlani, Maulud; Hakim, Muhammad Lukman; Wibisono, Mohammad Rico; Kurniawan, Muhammad Danu; Refta, Laddy Nafissa (Universitas Pahlawan Tuanku Tambusai, 2024)
Pasar Rebo District, East Jakarta City has an area of 12.98 , which is 6.90% of the area of East Jakarta City area of 188.03 , with 5 sub-districts, 53 RW and 525 RT and 221,158 people. The Million Orchid Village Program is the main icon of Pasar Rebo to promote its potential to the public. Program still faces several challenges in developing agribusiness and agro-tourism in realizing this program. For example, the orchid cultivation program is still in the pilot stage and funding has not yet been prepared properly, there is no proper business plan and there is limited land to build agribusiness and agro-tourism locations. The aim of this community service activity is to assist sub-district employees in creating business strategies using the canvas business model and SWOT method. The goal is to establish a village of a million orchids that relies on agribusiness and agro-tourism. The activity ended with a Focus Group Discussion, with recommendations for business strategy concepts.